Urban Stormwater Controls Operations and Maintenance. (Water Environment Federation, 2022)
The effectiveness of stormwater management programs depends largely on how well and how safely stormwater control measures (SCMs) perform over time. This manual provides best practices for the continued operation of SCMs, with a target audience of designers, utility managers, and O&M staff.
5.3 Gathering Cost Data.
Keywords: Urban runoff -- Management.; Storm sewers -- Maintenance and repair.; elektronické knihy; electronic books